2005
DOI: 10.1042/cs20040357
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution, plasma kinetics and quantification of single-pass pulmonary clearance of adrenomedullin

Abstract: The biodistribution, pharmacokinetics and multi-organ clearance of the vasodilator peptide AM (adrenomedullin) were evaluated in rats and its single-pass pulmonary clearance was measured in dogs by the indicator-dilution technique. Intravenously administered 125I-rAM(1-50) [rat AM(1-50)] was rapidly cleared following a two-compartment model with a very rapid distribution half-life of 2.0 min [95% CI (confidence interval), 1.98-2.01] and an elimination half-life of 15.9 min (95% CI, 15.0-16.9). The lungs retain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
(25 reference statements)
1
37
0
1
Order By: Relevance
“…Adrenomedullin is a multifunctional peptide mostly expressed in endothelial cells and distributed in various tissues, such as the lung, kidney, and heart (3,5). Previous studies have observed a high density of binding sites for adrenomedullin, with high affinity in lung tissues (4,5), which act as clearance receptors for the peptide (3,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenomedullin is a multifunctional peptide mostly expressed in endothelial cells and distributed in various tissues, such as the lung, kidney, and heart (3,5). Previous studies have observed a high density of binding sites for adrenomedullin, with high affinity in lung tissues (4,5), which act as clearance receptors for the peptide (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…When injected intravenously, adrenomedullin is predominantly cleared by pulmonary circulation by specific adrenomedullin receptors (2,3). Human and rat lungs indeed contain a high density of specific adrenomedullin binding sites (4,5), mostly distributed on the vascular endothelium.…”
mentioning
confidence: 99%
“…This value is comparable to the first-pass extraction of 30% 6 5% found in the present study with L-AM. We previously demonstrated that this represents specific binding as 125 I-AM clearance by the lungs of rats is displaced by AM (7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established that circulating AM is predominantly cleared by the pulmonary circulation through specific endothelial receptors (7)(8)(9). The AM receptor is a heterodimer composed of the calcitonin receptor-like receptor and receptor activity-modifying protein 2, both of which are highly expressed in the lungs (1,5).…”
mentioning
confidence: 99%
“…AM, a peptide from the calcitonin family, allows specific lung imaging through binding with its specific receptor, AM1 (CRLR/RAMP2), which is expressed at a high density in pulmonary vessels (6,7). Enhanced imaging efficiency can be associated with cell internalization after activation of the receptor by its agonist (8,9), but this process is also correlated with inherent biologic activity.…”
mentioning
confidence: 99%